Reevaluating the Impact of University Reputation on Job Employment: A Structural Equation Modeling Approach - Shannaq, Boumedyen; AlMaqbali, Said; Leow, Meng-Chew; H. Marhoubi, Asmaa; Ong, Lee-Yeng (Emerging Science Journal, 2025)
This paper examines the impact of university reputation on the employment of new graduates in Oman through industry linkages in higher education. Given that employability worldwide is connected to the reputation of universities, this study seeks to determine whether a similar situation exists in Oman. Specific indirect effects using Structural Equation Modelling (SEM) are evaluated based on research into particular factors affecting graduate employment. The survey was structured and yielded responses from graduate students. Of these, 76.6% were employed, while the remaining 23.4% reported being unemployed or unable to find work. Findings reveal that student performance and competency significantly influence internship opportunities, which in turn enhance job employment (SP  IO  JE:  = 0. 067, p = 0. 001; SC  IO  JE:  = 0.1, p <0.001). However, the university's reputation regarding employment through industry partnerships was found to be negative and insignificant (UR  IP  JE:  = 0. 011, p = 0. 072). This implies that while partnering with industries may alleviate unemployment in Oman, as is well known in Western countries, aligning universities with weak reputations for students’ employment chances may not yield satisfactory outcomes in Oman. Consequently, the study advocates for improving the relationship between universities and industries in Oman. Policymakers and academic institutions must focus on skills training, marketable skills, curriculum relevance, and increased internship opportunities for graduates. Furthermore, enhancing structures for organized employer assurances and assemblies to support long-established university graduates could strengthen universities' reputations in Oman. The study emphasizes the importance of improving the relationship between universities and industries in Oman. Therefore, policymakers and academic institutions must concentrate on skills training, marketable skills, curriculum relevance, and expanded internship opportunities for graduates. Additionally, enhancing frameworks for organized employer assurances and assemblies to support long-established university graduates could reinforce the university's reputation in the job market.